2022
DOI: 10.1159/000526769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Skin Permeability of Cannabidiol and Its Topical Formulations by Skin Membrane-Based Parallel Artificial Membrane Permeability Assay and Franz Cell Diffusion Assay

Abstract: <b><i>Introduction:</i></b> Cannabinoids including cannabidiol (CBD) have attracted enormous interest as bioactive ingredients for various dermatological and/or cosmeceutical uses. However, topical applications of cannabinoids might be limited without a fundamental understanding of their skin permeability. Herein, we aimed to evaluate the skin permeability of CBD and its topical formulations using artificial skin membrane assays. The solubility and stability of CBD in various surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Our group reported that CBD can suppress the activation of the NLRP3 inflammasome in human monocytes via the regulation of the P2X7 receptor. 14 In addition, our study showed that CBD is skin permeable, 13 and it can protect human skin cells (keratinocytes) from hydrogen-peroxide-induced oxidative stress through the modulation of the caspase-1−IL-1β axis. 15 However, whether CBD can exert protective effects via the inhibition of ferroptosis in human skin cells remains unknown.…”
mentioning
confidence: 74%
“…Our group reported that CBD can suppress the activation of the NLRP3 inflammasome in human monocytes via the regulation of the P2X7 receptor. 14 In addition, our study showed that CBD is skin permeable, 13 and it can protect human skin cells (keratinocytes) from hydrogen-peroxide-induced oxidative stress through the modulation of the caspase-1−IL-1β axis. 15 However, whether CBD can exert protective effects via the inhibition of ferroptosis in human skin cells remains unknown.…”
mentioning
confidence: 74%
“…This situation ensures minimal or no interaction between the active ingredient (e.g., CBD) and the other chemical ingredients in the formulation, such as waxes, surfactants (emulsifiers), oils, rheology modifiers, and water. 39 Thus, the most probable parameters that can affect the stability of CBD in the formulation are pH, temperature, as well as external environmental factors (frequency of light radiation, oxidation, humidity etc.) as previously mentioned in this section.…”
Section: Resultsmentioning
confidence: 99%
“…In the Franz diffusion cell assay, THCBD ( 4 ) has shown good skin permeability (Figure ) and found that ∼4000 μg gets traversed over a period of 3 h and, during that time, THCBD ( 4 ) exhibits a steady-state flux of 254.32 μg·cm –2 ·h –1 . On the other hand, CBD ( 1 ) traversed only 47.6–51.8 μg over a time of 6–12 h in the Franz diffusion cell assay . THCBD ( 4 ) has shown a better permeability profile than CBD ( 1 ) and presents a suitable candidate for topical application.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, CBD (1) traversed only 47.6−51.8 μg over a time of 6−12 h in the Franz diffusion cell assay. 58 THCBD (4) has shown a better permeability profile than CBD (1) and presents a suitable candidate for topical application.…”
Section: ■ Discussionmentioning
confidence: 99%